2021
DOI: 10.4185/rlcs-2022-1515
|View full text |Cite
|
Sign up to set email alerts
|

Calidad web en medios digitales: revisión bibliográfica sobre métodos e indicadores de evaluación general y atributos de confianza

Abstract: Introducción: Frente a la pérdida de confianza hacia los contenidos en internet, la desinformación, las noticias falsas y la crisis financiera que afecta a la prensa a nivel global, se revisan los estudios que proponen instrumentos dedicados a evaluar los sitios web de los medios digitales. Objetivos: Identificar y caracterizar los trabajos focalizados en el análisis de cibermedios, examinar sus métodos e indicadores, y revisar si estos consideran atributos de fiabilidad. Metodología: Se examina la producción … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
4
0
3
Order By: Relevance
“…Analyzing in communication channel the web page Morales et al, (2022), mention that it is a channel more used at present, by which it must meet the basic quality requirements, such as aspects of content, organization, virtual design of the interface and ease of use among others, so according to the results of this research the web page has a low correlation in satisfaction as a communication tool although it is true one of the proposals is that the IES must analyze so that this web page has impact and achieves the satisfaction of the educating caring quality criteria as the authors comment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyzing in communication channel the web page Morales et al, (2022), mention that it is a channel more used at present, by which it must meet the basic quality requirements, such as aspects of content, organization, virtual design of the interface and ease of use among others, so according to the results of this research the web page has a low correlation in satisfaction as a communication tool although it is true one of the proposals is that the IES must analyze so that this web page has impact and achieves the satisfaction of the educating caring quality criteria as the authors comment.…”
Section: Discussionmentioning
confidence: 99%
“…For Morales et al (2022), the web is the most used communication channel at present, which is why they must meet the basic quality requirements in aspects such as content, organization, visual design of the interface, and ease of use among others. This need has been maintained regardless of the continuous technological advances experienced such as the social web or the mobile web.…”
Section: Websitementioning
confidence: 99%
“…Specifically in the case of online media, the potential of which is the subject of this work, Morales-Vargas et al (2022) emphasise the pressing need for rigorous and reliable journalism amid the current widespread dissemination of fake news. However, their extensive review of quality indicators in this domain revealed a notable gap, specifically in assessing reliability indicators.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study on social media apps and their prospective role in geospatial research by Owuor & Hochmair (2020) sheds light on this aspect. Usability, defined as the achievement of learning objectives with specified resources in a particular environment, and accessibility, which involves adapting the learning environment to suit all learners' needs, are closely interrelated (Morales-Vargas et al, 2022).Romero Martínez et al (2022 previously highlighted that under optimal conditions, information and communication technologies have the potential to expedite, enrich, and deepen knowledge acquisition. Web 2.0 technologies encompass social networking sites, blogs, wikis, video sharing platforms, and hosted service web applications.…”
Section: Introductionmentioning
confidence: 99%